Antifungal Activity of Red Ginger (Zingiber officinale var. Rubrum) and Garlic (Allium sativum) against HIV Patients-Isolated Candida albicans - Erni Winarni; Ali Napiah Nasution; Sri Wahyuni Nasution (Postgraduate, University of Mataram, 2023)
The most of Candida strain in oral candidiasis is nystatin resistance strain. Hence, it become important to investigate the natural products like red ginger (Zingiber officinale var. Rubrum) and garlic (Allium sativum) as antifungal against HIV patient-isolated Candida albicans. This experimental study used two antifungal assays (Disc diffusion and antibiofilm assay). Both red ginger and garlic extract were extracted by maceration method. Candida albicans isolate was isolated from a volunteer HIV Patient with oral candidiasis. The outcomes included the diameter of the inhibition zone and optical density (OD) that were expressed as mean and standard deviation and analysed by Kruskal-Walis. This study showed that the highest concentration of both red ginger (0.67 ± 0.55 mm) and garlic extract (0.67 ± 0.46 mm) had the widest diameter of inhibition zone. Meanwhile, the highest inhibition of biofilm formation was found in the lowest concentrations (25%) of red ginger (2.22 ± 1.24) and garlic extract (3.65 ± 0.24). Any concentration of red ginger or garlic extract did not significantly affect the antifungal activity (P-Value: 0.392). Overall, it can be concluded that both red ginger and garlic extract at any concentration showed a weak antifungal activity against HIV patient-isolated Candida albicans strain.